2008
DOI: 10.1177/1420326x08089260
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Environmental Interference with Airborne Bacteria and Fungi Levels in Air-Conditioned Offices

Abstract: Indoor airborne bacteria and fungi levels can be selected as indicators of a healthy indoor environment. This study investigated the relationships between the airborne bacteria levels, fungi levels, and thermal environmental parameters, i.e., air temperature and relative humidity, in some offices with a Mechanical Ventilation and Air-Conditioning (MVAC) system operating. A total of 101 samples were collected from two typical Hong Kong air-conditioned office premises. There was evidence that the operation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…There was a significant correlation (r=0.487; p=0.014) between temperature and the level of fungal contamination (CFU/m 3 ), similar to other studies [18,19], and corroborating the temperature influence in the fungal growth.…”
Section: Discussionsupporting
confidence: 72%
“…There was a significant correlation (r=0.487; p=0.014) between temperature and the level of fungal contamination (CFU/m 3 ), similar to other studies [18,19], and corroborating the temperature influence in the fungal growth.…”
Section: Discussionsupporting
confidence: 72%
“…It was found that the relationship between the fungal air contamination and the temperature and relative humidity was not statistically significant (p>0,05) in both schools, despite results obtained from others studies [12,13]. This may be justified by the effect of other environmental variables also influencing fungal spreading, namely the occupants' number [24], as well the developed activities that may also affect fungal concentration [25].…”
Section: Discussionmentioning
confidence: 48%
“…A study conducted revealed peaks of fungal spores in the outside air, with temperatures of between 22ºC and 27ºC and humidity between 75 and 80%, and smaller quantities of fungal spores with temperatures of between 43ºC and 48ºC and humidity between 25 and 40% [11]. Moreover, Wong et al and Strachan et al also found an air fungal contamination increase with high values of temperature and humidity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the prediction results of fungal index; especially in mycelium length of E. herbariorum, were also used to evaluate the sensitivity of the reaction diffusion model. Furthermore, in this research, fungal index was used as the damping function (T, '), determined by Equation (6) for the reaction diffusion model. In the condition that the fungal index (mycelium length) was assumed to be a dependent variable, and temperature and relative humidity were assumed as independent variables, the approximate expression (T, ') based on isopleth diagrams of fungal index was assumed using the non-linear and minimumsquare approximation method.…”
Section: Prediction Of Hyphal Growth By Fungal Indexmentioning
confidence: 99%
“…Many published studies have confirmed the presence of fungal contamination in indoor environments and it has been reported that fungal spores and microbial volatile organic compounds (MVOCs) emitted from fungi have adverse health effects [1][2][3][4][5][6][7][8]. Fungal growth in indoor environments is strongly related to the indoor physical and chemical conditions, such as atmospheric air temperature, relative humidity, hydrogen-ion exponent (pH) in free water and nutrients; therefore, a comprehensive prediction method must be developed to estimate fungal growth and the subsequent health risk of fungal contamination for exposed individuals.…”
Section: Introductionmentioning
confidence: 99%